2022
DOI: 10.1111/vru.13184
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography evaluation of cats with chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a major health condition in cats that can lead to poor quality of life and financial implications for therapy. Currently staging and identification of CKD is limited by diagnostic testing such as creatinine and urine‐specific gravity, which do not change until late in the disease course. Other methods to evaluate CKD would be valuable in the clinical setting. Shear wave elastography is one novel ultrasound method, which has shown promise in identifying increases in tissue stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In human medicine, multiple studies have described an increased RS in patients with CKD [ 32 , 35 , 42 ], and a recent meta-analysis about the use of SWE in these patients, has shown that this technique is highly accurate, and has clinical significance for evaluating and diagnosing renal fibrosis [ 39 ]. In veterinary medicine, four studies have been carried out for the evaluation of RS in course of CKD, two in cats and two in dogs [ 1 , 13 , 55 , 56 ]. In the studies carried out on dogs, higher 2D-SWE values were observed in patients with CKD [ 13 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human medicine, multiple studies have described an increased RS in patients with CKD [ 32 , 35 , 42 ], and a recent meta-analysis about the use of SWE in these patients, has shown that this technique is highly accurate, and has clinical significance for evaluating and diagnosing renal fibrosis [ 39 ]. In veterinary medicine, four studies have been carried out for the evaluation of RS in course of CKD, two in cats and two in dogs [ 1 , 13 , 55 , 56 ]. In the studies carried out on dogs, higher 2D-SWE values were observed in patients with CKD [ 13 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shear wave elastography (SWE) is a non-invasive, ultrasonographic method, which has gained interest in the evaluation of renal parenchymal elasticity, both in human and veterinary medicine [ 1 , 13 , 25 , 29 , 44 , 49 , 55 , 56 ]. Moreover, in veterinary medicine, the use of SWE has been focused predominantly on the assessment of the liver parenchyma, but also in the evaluation of lymphnodes, mammary nodular lesions, pancreas, spleen, intestinal wall, and muscles [ 7 , 18 , 37 , 50 , 51 , 52 , 57 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of shear wave elastography in diagnosing CKD remains quite controversial in humans [ 11 ]. In veterinary medicine, few studies have been reported to assess the application of SWE in CKD [ 2 14 15 ]. Previous studies revealed that CKD groups had a higher renal SWV than control groups in dogs and cats [ 2 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that CKD groups had a higher renal SWV than control groups in dogs and cats [ 2 15 ]. In contrast, another feline study revealed that there was no significant difference in renal SWV between groups [ 14 ]. Considering the controversy regarding feasibility of SWE in CKD, subsequent studies are warranted in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%